Effect of NaOH impregnation on the electrochemical performances of hard carbon derived from olive seeds biomass for sodium ion batteries. (2022) - Bensouda, H.; Hakim, C.; Aziam, H.; Bacaoui, A.; Saadoune, I.
Abstract: Olive seeds were evaluated as potential precursors for Hard Carbon preparation using two synthesis methods: standard pyrolysis at 1000 °C and chemical pretreatment with NaOH followed by pyrolysis at 1000 °C. Every sample was characterized and tested as a negative electrode for Na-ion batteries to investigate the influence of NaOH impregnation on the hard carbon properties and on their electrochemical performances. Herein, a hard carbon anode derived from NaOH-impregnated olive seed exhibits a reversible capacity of 147 mAh/g with a superior stable capacity retention of 97% over 15 cycles. The improvement of the cycling performances of NaOH-impregnated hard carbon compared to non-treated hard carbon can be explained by the formation of more active sites for sodium intercalation between the graphene layers.